2020
DOI: 10.3897/phytokeys.154.51454
|View full text |Cite
|
Sign up to set email alerts
|

Welcome to the Czech Republic again! Rare northern mosses Calliergon megalophyllum and Drepanocladus sordidus (Amblystegiaceae) in South Bohemia in light of their European distribution and habitat preferences

Abstract: Two aquatic moss species, Calliergon megalophyllum and Drepanocladus sordidus (Amblystegiaceae, Bryophyta), which had been considered extinct in the Czech Republic, were found in the Třeboň Basin, South Bohemia, in 2016–2017. They co-occurred in extensive reed- and sedge-dominated fen pools with humic water on the shore of an old fishpond and the former species was also discovered in a small humic pool in an old shallow sand-pit. The new Czech sites of these rare boreal species represent one of the southernmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Studies in Scandinavia found male buds and sporophytes in only ~ 4% of 224 specimens studied (Bisang et al 2014). The absence of males is a classic condition explaining the frequent sterility of dioecious bryophytes (Hedenäs et al 2010, Bisang et al 2014, among which are many wetland species, including D. turgescens (Hedenäs 2002, Porley 2013, Hedenäs et al 2016, Campbell et al 2019, Krajewski et al 2020. However, even if we could not detect males, it is still possible that they are present as sterile colonies, so called "shy males", not expressing their sexual parts (Stark et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Scandinavia found male buds and sporophytes in only ~ 4% of 224 specimens studied (Bisang et al 2014). The absence of males is a classic condition explaining the frequent sterility of dioecious bryophytes (Hedenäs et al 2010, Bisang et al 2014, among which are many wetland species, including D. turgescens (Hedenäs 2002, Porley 2013, Hedenäs et al 2016, Campbell et al 2019, Krajewski et al 2020. However, even if we could not detect males, it is still possible that they are present as sterile colonies, so called "shy males", not expressing their sexual parts (Stark et al 2010).…”
Section: Discussionmentioning
confidence: 99%